THE FLIPPED CLASSROOM MODEL: EXPLORING THE EFFECT ON THE KNOWLEDGE RETENTION OF MEDICAL STUDENTS - Alnahdi, Mesedah; Agha, Sajida; Khan, Muhammad Anwar; Almansour, Mubarak (Journal of Ayub Medical College Abbottabad, 2022)
Background: In the Middle East, where most of the higher learning institutions still focus on the teacher-centred approach, implementation of this pedagogical model is an enormous task for educators. This study was designed to assess the role that the flipped classroom modality plays in the knowledge retention of medical students with a background in traditional methods of teaching and learning. Methods: This study employed a mixed study design among a sample of 3rd year medical students (n=193) in the neurosciences course block. The students were divided into two groups: experimental and control. A post-test, a questionnaire, and semi-structured interviews as research instruments were used to collect data in this study. Results: The results revealed a significant mean difference between the post-test scores in traditional (4.1±0.98) and flipped classroom (3.6±1.03) with a p-value=0.01, while no mean difference was found between male and female students (3.9±1.04, 3.9±1.02, p-value=0.77). The students appreciated the flipped classroom modality that helped with information sharing, interaction with peers and learning from others' experiences. Correspondingly, the four main characteristics of flipped classroom emerged from the thematic analysis: (1) positive perceptions of the flipped classroom, (2) challenges of the flipped classroom, (3) the effects of personal characteristics, and (4) lack of administration support. Conclusion: The performance of students was better in the traditional class than in the flipped classroom, particularly in the cognitive areas that deal with the interpretation and application of knowledge. The students taking responsibility for their own learning in this new modality and the short duration of the study might have had some influence on the study results. Future in-depth studies are recommended